2019
DOI: 10.1186/s12871-018-0674-6
|View full text |Cite
|
Sign up to set email alerts
|

Conditions for laryngeal mask airway placement in terms of oropharyngeal leak pressure: a comparison between blind insertion and laryngoscope-guided insertion

Abstract: BackgroundInsertion under laryngoscopic guidance has been used to achieve ideal positioning of the laryngeal mask airway (LMA). However, to date, the efficacy of this technique has been evaluated only using fiberoptic evaluation, and the results have been conflicting. Other reliable tests to evaluate the efficacy of this technique have not been established. Recently, it has been suggested that the accuracy of LMA placement can be determined by clinical signs such as oropharyngeal leak pressure (OPLP). The aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 22 publications
2
20
0
1
Order By: Relevance
“…Kim et al showed that the rate of success at the first attempt was similar between standard digital and laryngoscope-guided insertion [14]. However, many other studies that used different LMA types indicated that the laryngoscope-guided insertion technique is more successful than were the digital or rotational techniques [8, 11, 14, 15, 23]. Additionally, the laryngoscope-guided, gum elastic bougie-guided technique was superior to the digital and introducer technique [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim et al showed that the rate of success at the first attempt was similar between standard digital and laryngoscope-guided insertion [14]. However, many other studies that used different LMA types indicated that the laryngoscope-guided insertion technique is more successful than were the digital or rotational techniques [8, 11, 14, 15, 23]. Additionally, the laryngoscope-guided, gum elastic bougie-guided technique was superior to the digital and introducer technique [4].…”
Section: Discussionmentioning
confidence: 99%
“…It was first reported by Lee that the laryngoscope can improve the placement of LMA in an adult [10]. Then, direct laryngoscopy alone or laryngoscope-assisted guided techniques were used for this purpose [4, 8, 1114]. These methods do have theoretical disadvantages, such as haemodynamic and airway stimulation and pharyngeal or oesophageal trauma [4, 8].…”
Section: Introductionmentioning
confidence: 99%
“…21 20,22 Penelitian Kim dkk (2019) menyebutkan bahwa hal ini berkaitan teknik laringoskopi untuk memfasilitasi insersi LMA dengan cara mengangkat dengan lembut (gentle) epiglotis dan tidak diperlukan untuk membuka rongga trakeal atau pita suara (glotis). 23,24 Selain daripada itu, keuntungan teknik insersi LMA laringoskopi tidak memerlukan bantuan asisten untuk melakukan insersi. Sedangkan pada teknik insersi TAM diperlukan asisten untuk melakukan manipulasi TAM.…”
Section: Pendahuluanunclassified
“…2 LMAs have been used widely during general anesthesia, they have certain benefits over conventional bag mask ventilation in terms of freeing anesthetist′s hands and lesser complications. 3 Rather than crossing the vocal cords like endotracheal tube it sits over the cords. It is equally useful both in elective and emergency surgeries as well in adults and children.…”
Section: Introductionmentioning
confidence: 99%